Analysis of language and legal rights within the Scandinavian debate. Human rights: a “hidden essence”? - Serpe, Alessandro (Frónesis)
The new approach of analytical jurisprudence was in line with the tradition of Scandinavian realism. My contribution addresses the search for differences and similarities by describing the contribution of Scandinavian authors on legal rights and more explicitly their ontological and semantic nature, the issues of a definition and its practical utility within the legal system. The debate on legal rights arose in the 40”™s may be considered as still actual in the sense that the semantic and pragmatic approach has nowadays involved the issues concerning the nature of human rights. It is recognizable in the debate on human rights a pragmatic approach on the subject seem to predominate. Pragmatic and realistic instances get the upper hand. The definition of a theoretical concept (as “human right” or “legal right”) does not say anything concerning the content and moreover the forms of protection or the immunities which should be stated as fundamental. Scandinavians seem to avoid ontological-substantial definitions.